PELATIHAN PEMBUATAN IKLAN PENYULUHAN BERBASIS APLIKASI CANVA DI KECAMATAN SAKO PALEMBANG - Selvia Aprilyanti; Hariman Al Faritzie; Azhari Azhari (Universitas Mataram, 2023)
A media for promoting advertising of an activity or item, one of which is based on the Canva application. Canva is an application in the field of graphic design. Based on a field survey, staff and the community in Sako District, Palembang City, do not yet understand promotional media independently using digital advertising based on the Canva application to design and create promotional media or outreach activities. For this reason, this community service activity is carried out through counseling and training on the use of the Canva application. With the aim of providing education to office staff in creating outreach or promotional media using digital advertising. It is hoped that this activity can help the community in spreading or promoting their activities through digital media. This service activity was carried out at the Sialang Village Head Office, Sako District, Palembang City for partners totaling 30 residents. The implementation method consists of several stages, including coordination with partners, material counseling and training. The results of this training were the level of understanding of partners who took part in the activity. The participants practice directly according to the directions of the training material. Evaluation of the activities carried out was the distribution of questionnaires with several indicators, namely ease of use, clarity of material presented, and benefits felt by participants. Of the total of 30 participants, 33% of the participants had understood a little of the counseling material and 67% of the participants had really understood the counseling material regarding the utilization and use of the Canva application. Evaluation of the activities carried out was the distribution of questionnaires with several indicators, namely ease of use, clarity of material presented, and benefits felt by participants. A significant increase occurred in partner knowledge. The Canva application will help partners create interesting and persuasive outreach media.